Politicizing Presidential Impeachment in the Contemporary World - I. Zaznaev, Oleg (International Journal of Criminology and Sociology, 2022)
The role and importance of the president is growing in contemporary society; therefore, more is demanded of him. A request for the responsibility of the president in the form of impeachment has appeared in society. Usually impeachment is mainly considered a legal procedure with purely legal causes - the commission of a crime or a serious offense. However, in many countries today, we can observe the politicization of impeachment. This article deals with the problem of the politicization of impeachment, which is poorly addressed in scientific literature. The author provides arguments in defense of this thesis: the politicization of articles of impeachment and their broader interpretation, which allows finding the corpus delicti in almost any action of the president; politicization of the impeachment procedure; and the dependence of the beginning, course and outcome of impeachment on the alignment of party forces. The author concludes that modern impeachment is actually a vote of no confidence in the legal shell: legal aspects of impeachment are replaced by political ones. In this regard, the issue of simplifying the impeachment procedure and turning it into the routine way of terminating presidential powers is relevant.